2019
DOI: 10.1038/s41598-019-52230-5
|View full text |Cite
|
Sign up to set email alerts
|

3D Porous Graphene Based Aerogel for Electromagnetic Applications

Abstract: Lightweight multifunctional electromagnetic (EM) absorbing materials with outstanding thermal properties, chemical resistance and mechanical stability are crucial for space, aerospace and electronic devices and packaging. Therefore, 3D porous graphene aerogels are attracting ever growing interest. In this paper we present a cost effective lightweight 3D porous graphene-based aerogel for EM wave absorption, constituted by a poly vinylidene fluoride (PVDF) polymer matrix filled with graphene nanoplatelets (GNPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…As a consequence, the PVDF/GNP composite film morphology varies notably with respect to the one of the neat PVDF, from a round shape structure to a more compact configuration. Hence, the film porosity decreases noticeably, improving the waterproofness of the nanocomposite [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and its mechanical and electrical characteristics [39,40]. Indeed, it has also been found that GNPs have a nucleation effect on the PVDF structure, constraining the polymer chains to orient and close pores [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the PVDF/GNP composite film morphology varies notably with respect to the one of the neat PVDF, from a round shape structure to a more compact configuration. Hence, the film porosity decreases noticeably, improving the waterproofness of the nanocomposite [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and its mechanical and electrical characteristics [39,40]. Indeed, it has also been found that GNPs have a nucleation effect on the PVDF structure, constraining the polymer chains to orient and close pores [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their outstanding properties, GNP-filled polymer composites have been widely investigated in various engineering applications, including electromagnetic compatibility [18][19][20], structural sensing and monitoring [21][22][23][24]. Different polymer matrices have been explored, such as polystyrene [17,20], epoxy-based vinyl ester resins [18,19,24], polydimethylsiloxane [5,22], polyurethane [25], and polyvinylidene fluoride (PVDF) [23,24,[26][27][28]. Among them, PVDF is garnering ever growing interest for sensing applications owing to its uncommon chemical resistance and thermal mechanical physical properties, including piezoresistive and piezoelectric ones [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and its derivatives can be used as building blocks to make such 3D structures. Graphene aerogels, also commonly known as aerographene, are widely used in polymer composites to enhance thermal [170,171], electrical [172,173], tribological [174,175] and mechanical properties of the polymer. For example, Kim et al [176] reported a maximum improvement of 76% in the fracture toughness of non-oxidized graphite aerogel (NOGA)/epoxy composite at a loading level of 0.45vol.% as compared to neat epoxy.…”
Section: D-2d Hybridsmentioning
confidence: 99%
“…In this work, we tackled these challenges by developing a direct method to produce highly porous bulk PVDF aerogels with precise control of the phase composition, without further sample processing or the incorporation of a template. The limited available research on PVDF aerogels is focused on porous membranes [ 27 , 28 , 29 ], adsorbent media [ 30 , 31 , 32 ], composites [ 33 , 34 , 35 ], thermal insulation [ 36 ], and airborne particle filtration [ 16 , 37 ], mostly prepared by phase separation approaches using different solvents, followed by supercritical drying process, or in some cases by freeze drying, without meaningful attention on controlling the crystalline phases, somehow demonstrating that this porous system is seemingly ignored for piezoelectric applications. Consequently, an in-depth study on phase control has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%